Numerical modeling the impacts of increasing groundwater pumping upon discharge decline of the BL Spring located in Xilin Gol League in east inner Mongolia, China - Xiao, Han; Yang, Yu; Liu, Qiyuan; Zang, Yongge; Lian, Xinying; Xia, Fu; Jiang, Yonghai (Frontiers in Environmental Science, 2024)
Please see attached file.